Island contributions to disaster research. (1st April 2015) - Kelman, Ilan; Lewis, James; Gaillard, J.C.; Mercer, Jessica
Abstract : Island case studies have contributed significantly to disaster research theory and application, including more recent work on climate change adaptation. Island-related work in development and disasters has been particularly adept at building on the past in order to create a better development future through disaster risk reduction, one subset of which is climate change adaptation. However, recent emphasis on climate change has to a large degree bypassed previous and deeper understandings of island contributions to disaster research as well as the importance of island situations. This paper details key elements from the literature on island-based development and disaster research – especially regarding the themes of vulnerability and resilience theory as then applied in practice for island migration – linking this material with a critiquing analysis of ongoing work emerging from climate change. Despite the importance of dealing with climate change, especially for islands and islanders, it must always be placed within wider disaster and development tasks. This includes embracing previous work in order to learn from, without becoming mired in, the past.